2021
DOI: 10.1371/journal.pone.0246786
|View full text |Cite
|
Sign up to set email alerts
|

Signs of neuroaxonal injury in preeclampsia—A case control study

Abstract: Background Cerebral injury is a common cause of maternal mortality due to preeclampsia and is challenging to predict and diagnose. In addition, there are associations between previous preeclampsia and stroke, dementia and epilepsy later in life. The cerebral biomarkers S100B, neuron specific enolase, (NSE), tau protein and neurofilament light chain (NfL) have proven useful as predictors and diagnostic tools in other neurological disorders. This case-control study sought to determine whether cerebral biomarkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…Recently published results from our research group reported increased concentrations of NfL in both plasma and CSF in women with preeclampsia compared with normotensive pregnant women. In addition, there was a strong correlation between concentrations of NfL in plasma and CSF [ 42 ]. Previous studies of women with preeclampsia have not been able to establish whether a BBB impairment exists in these women or not [ 43 ]; however, human studies are few on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published results from our research group reported increased concentrations of NfL in both plasma and CSF in women with preeclampsia compared with normotensive pregnant women. In addition, there was a strong correlation between concentrations of NfL in plasma and CSF [ 42 ]. Previous studies of women with preeclampsia have not been able to establish whether a BBB impairment exists in these women or not [ 43 ]; however, human studies are few on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…In one study that had previously investigated the CSF/plasma albumin ratio, 15 women with preeclampsia and 15 women with normotensive pregnancies were included. There were no women with eclampsia in this study [ 15 ]. One woman in the preeclampsia group had HELLP syndrome but none had eclampsia or other severe end organ complications.…”
Section: Discussionmentioning
confidence: 99%
“…In the normotensive group, the CSF/plasma albumin ratio was 2.73, similar to our findings of 3.1. Women with preeclampsia had a median CSF/plasma albumin ratio of 3.02 [ 15 ]. In our study, the median CSF/plasma albumin ratio in women with preeclampsia was 5.2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 In another study, women with preeclampsia without clinically detectable neurological complications had increased CSF and plasma concentrations of NFL compared to women with normotensive pregnancies. 15 However, scant information is currently available regarding the origin, importance, and role of sNFL, and there are no reliable blood tests to predict eclampsia- or preeclampsia-induced cerebral edema. Furthermore, few data exist on sNFL in term and preterm infants.…”
Section: Main Textmentioning
confidence: 99%